Pengaruh Akuntabilitas dan Transparansi Pengelolaan Keuangan terhadap Kepercayaan Muzakki dalam Membayar Zakat di BAZNAS Kabupaten Batang Hari - Viona Zahara Monica Nurkumala; Faturahman Faturahman (ARZUSIN, 2026)
Although accountability and transparency in zakat management have received attention in various studies, research that specifically places muzakki trust in the context of BAZNAS Batang Hari Regency remains limited. This study aims to analyze the influence of accountability and financial management transparency on muzakki trust in paying zakat at BAZNAS Batang Hari Regency. This study used a quantitative approach with a survey design, involving 98 muzakki as respondents selected using non-probability sampling based on specific criteria. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, and were then analyzed using multiple linear regression with the assistance of SPSS. The results showed that accountability had a positive but non-significant effect on muzakki trust, whereas transparency had a positive and significant effect. Simultaneously, accountability and transparency had a positive and significant effect on muzakki trust. These findings confirm that information openness and institutional accountability are important factors in building muzakki trust in zakat management. The implications of this study provide practical contributions for BAZNAS Batang Hari Regency in improving the quality of reporting, public information access, and institutional communication on an ongoing basis to strengthen muzakki trust.